The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1055/s-0036-1584326
|View full text |Cite
|
Sign up to set email alerts
|

Interosseous Membrane of the Forearm

Abstract: There are multiple methods for treating patients with IOM injuries. Physicians should be highly suspicious about this injury when a patient presents with a highly displaced radial head fracture associated with wrist pain. Treatment with reconstruction of the cerebral band of the IOM with radial head replacement (do not overstuff) and temporary uploading the construct with K-wires from the ulna to the radius will give the most predictable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Transverse and longitudinal stability is necessary for the human forearm, which is viewed as a dynamic structural entirety. [6] To accomplish accurate and remarkable tasks, the forearm bones must act as a single functional unit in consort with the interosseous membranes and ipsilateral radioulnar joints. Anatomical restoration and stable fixation are mandatory in the treatment of any forearm fracture, which should be treated in an equivalent manner as an intraarticular fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Transverse and longitudinal stability is necessary for the human forearm, which is viewed as a dynamic structural entirety. [6] To accomplish accurate and remarkable tasks, the forearm bones must act as a single functional unit in consort with the interosseous membranes and ipsilateral radioulnar joints. Anatomical restoration and stable fixation are mandatory in the treatment of any forearm fracture, which should be treated in an equivalent manner as an intraarticular fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the interosseous membrane contributes to the stability of the forearm. Interosseous membrane rupture may cause humeroradial joint and ulnocarpal joint impaction, elbow and wrist pain, and limited forearm movement [21][22][23] . Gutowski et al 24 reported that the values for supination and pronation increased by 26% and 22%, respectively, after cutting the interosseous membrane of the forearm.…”
Section: Repairing the Coronacloid Fracturementioning
confidence: 99%
“…It can occur at 3 different locations: (1) within the supinator muscle, close to the radial tuberosity, in the case of insufficient intraoperative washing; (2) at the opposite side of the radial tuberosity, in the case of extensive drilling, resulting in cortical effraction; and (3) close to the proximal radioulnar joint, in the case of a proximal interosseous membrane lesion. In the third location, proximal radioulnar synostosis may also develop . Ultrasonography shows heterotopic ossification earlier than does radiography, showing hyperechoic nodules or streaks with posterior acoustic attenuation within muscles .…”
Section: Imaging Appearance Of Surgical Complicationsmentioning
confidence: 99%
“…In the third location, proximal radioulnar synostosis may also develop. 9,38 Ultrasonography shows heterotopic ossification earlier than does radiography, showing hyperechoic nodules or streaks with posterior acoustic attenuation within muscles. 9,10,39 Indomethacin and radiotherapy have been used in an effort to prevent heterotopic ossification.…”
Section: Imaging Appearance Of Surgical Complicationsmentioning
confidence: 99%